2013
DOI: 10.1890/12-0247.1
|View full text |Cite
|
Sign up to set email alerts
|

Increased nitrogen cycling facilitates native forest regeneration: Potential for restoring extinct ecological processes?

Abstract: Ecological processes often maintain the plant communities with which they have a long evolutionary association, and so their loss may favor invasions by nonnative species. We simulated the effects of fecal deposition and soil turnover by the extinct avian megafauna of New Zealand to test their influence on woody plant regeneration and nonnative plant invasion in a cool temperate rain forest. Hen manure increased soil available NO3-, leading to greater seedling regeneration relative to control plots. Although s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…First, there has been significant debate about the role of moa herbivory in the evolution of plant structural (e.g., wire-plant syndrome) and developmental (e.g., heteroblasty) characteristics in the New Zealand flora (19)(20)(21)(22)(23)(24)(25). Second, there is increasing interest in the legacy that moa extinction may have had on indigenous vegetation community structure and composition (18,26) based on a…”
mentioning
confidence: 99%
“…First, there has been significant debate about the role of moa herbivory in the evolution of plant structural (e.g., wire-plant syndrome) and developmental (e.g., heteroblasty) characteristics in the New Zealand flora (19)(20)(21)(22)(23)(24)(25). Second, there is increasing interest in the legacy that moa extinction may have had on indigenous vegetation community structure and composition (18,26) based on a…”
mentioning
confidence: 99%
“…This may be an opportunity for modern experimentation to test a paleoecological hypothesis; in a recent test simulating the impacts of the New Zealand moa extinction on nitrogen cycles, Tanentzap et al . () found that avian‐derived nitrogen inputs increased native forest regeneration.…”
Section: Ecological Consequences Of the Late Quaternary Extinctionsmentioning
confidence: 99%
“…Additionally, any sedimentary proxy will integrate processes at the watershed level, and so differentiating spatial heterogeneity at the sub-watershed scale will likely not be possible. This may be an opportunity for modern experimentation to test a paleoecological hypothesis; in a recent test simulating the impacts of the New Zealand moa extinction on nitrogen cycles, Tanentzap et al (2013) found that avian-derived nitrogen inputs increased native forest regeneration.…”
Section: Megafaunal Influences On Vegetation May Have Varied With Lanmentioning
confidence: 99%
“…Interestingly, previous published estimates of moa population density have had an extreme bimodal distribution, grouping into either low density (< 2 moa km −2 ) (Anderson 1989, Holdaway and Jacomb 2000, Forsyth et al 2010, Lee et al 2010 or high density (> 10 moa km −2 ) (Batcheler 1989, Caughley 1989, Gemmell et al 2004, Tanentzap et al 2013) estimates, with no intermediate ones (Fig. 3).…”
Section: Moa Population Estimatesmentioning
confidence: 88%
“…High density estimates (i.e. 30-46 total moa km −2 ) (Batcheler 1989, Caughley 1989, Gemmell et al 2004, Tanentzap et al 2013) seem unrealistic in that they are not remotely comparable to those of extant large ratites (Supplementary material Appendix 1 Table A1; see also Forsyth et al 2010), although we acknowledge that many extant species of ratites have been impacted directly and indirectly by human activity. These high-density estimates of total moa are, however, comparable to the densities of red deer Cervus elaphus recorded during their peak irruptive phase in New Zealand (ca 20-50 deer km −2 ), although these densities crashed as available food was depleted (Challies 1985).…”
Section: Moa Population Estimatesmentioning
confidence: 93%